Importance of Top Management Commitment to Organizational Citizenship Behaviour towards the Environment, Green Training and Environmental Performance in Pakistani Industries - Salman Bashir, Memon; Amran, Rasli; Abdul Samad, Dahri; Imelda Hermilinda, Abas (Molecular Diversity Preservation International (MDPI), 2022)
This research examines the interplay of green training, organisational citizenship behaviour toward the environment, top management commitment, and environmental performance in four different industrial units in Pakistan. These units have been implementing environmentally friendly policies and conforming their environmental activities to the regulatory framework of Pakistan’s National Environment Quality Standards in a sustainable manner. In particular, this research aims to ascertain how green training affects organisational citizenship behaviour toward the environment, and to evaluate the impact of top management commitment to environmental performance and green training. According to hypothesis testing results based on 222 key informants randomly recruited from the industry, green training positively relates to civic organisational behaviour toward the environment. In addition, top management commitment is entirely related to environmental performance. In contrast, green training is also positively associated with top management commitment. This study supports the ability motivation opportunity and resource-based view theories by demonstrating that top management commitment is a key factor in encouraging environmental performance and promoting green training that leads to organisational citizenship behaviour toward the environment. This study has several limitations, as the cross-sectional data were only from the manufacturing sector in Pakistan. The researchers strongly suggest that future studies use mixed-method research to understand the phenomenon better. Future researchers could conduct comparative research by using the current instrument in the service sector. Finally, future researchers could use multilevel modelling and potential moderators and mediators to constructively re-examine the model tested in this study by incorporating new variables accordingly.